BENTUK PENYAJIAN TARI JEPIN LANGKAH GERSIK PANTAI DI KOTA PONTIANAK KALIMANTAN BARAT - Huda, Nurul; Ismunandar, Ismunandar; Silaban, Christianly Yeri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe background of this research are to  know and to understand deeper about the form of the performance of Jepin Langkah Gersik Pantai dance, including the range of motion, accompaniment music, cosmetology, and the clothes Also, upper and under design, and the place to show. The methodology of this research is descriptive qualitative method with choreography approach. The results of this research are 1. Jepin Langkah Gersik Pantai at Pontianak West Kalimantanis represented the life of the people who live near the beach. 2. Jepin Langkah Gersik Pantai is divided into three categories those are first movement (pantai) second movement (nyusor arus), last movement (nyusor gelombang). 3. The numbers of the dancers should be in even numbers and consist of men and women. 4. The instruments of this dance are beruas, violin, accordion, and gambus. 5. Jepin Langkah Gersik Pantai dance is using realistic cosmetics. 6. The uniform of the women?s dancers consist of telok belange clothes, corak insangstuff,  kembang goyang stuff and the last is flowers. 7 the uniform of the men?s dancers are consist of telok belanga clothes and corak insang pants. Keywords: Presentation, Jepin Langkah Gersik Pantai dance